Estudo da influência do itérbio na conversão ascendente de frequências do praseodímio em nanocristais com base em óxido de alumínio - Barreto, Pâmella Gonçalves (2009)
This work of master's degree was concentrated in the analysis of the structural and optical properties of dielectric nanocristals (NCs) based on aluminum oxide doped with rare-earths trivalent ions praseodymium (Pr3+) and ytterbium (Yb3+) and prepared by combustion technique. These ions are luminescent in hosts that present a band-gap in the ultraviolet region. We studied the up conversion (UC) of optical frequencies from the infrared to the visible in these NCs using samples with different concentrations of Pr3+ and Yb3+. The analysis of x-ray diffraction showed that the samples are polycrystalline with changes of the crystal phases with the doping concentration. The study of the luminescence also demonstrated different mechanisms of UC with the doping concentration. These mechanisms will be interpreted in accordance with the concepts presented along the dissertation.